Construction and Transposon Mutagenesis in Escherichia coli of a Full-Length Infectious Clone of Pseudorabies Virus, an Alphaherpesvirus - Smith, Gregory A. (American Society for Microbiology, 1999)
A full-length clone of the 142-kb pseudorabies virus (PRV) genome was constructed as a stable F plasmid in Escherichia coli. The clone, pBecker1, was colinear with PRV-Becker genomic DNA, lacking detectable rearrangements, deletions, or inversions. The transfection of pBecker1 into susceptible eukaryotic cells resulted in productive viral infection. Virus isolated following transfection was indistinguishable from wild-type virus in a rodent model of infection and spread to retinorecipient regions of the brain following inoculation in the vitreous body of the eye. Mutagenesis of pBecker1 in E. coli with a mini-Tn5-derived transposon enabled the rapid isolation of insertion mutants, identification of essential viral genes, and simplified construction of viral revertants. The serial passage of a viral insertion mutant demonstrated the transposon insertion to be stable. However, the F-plasmid insertion present in the viral gG locus was found to undergo a spontaneous deletion following transfection into eukaryotic cells. The implications of F-plasmid insertion into the viral genome with regard to phenotype and genomic stability are discussed.